The Pallbearer - Katims, Jason 1960-; Reeves, Matt 1966-; Abrams, Jeffrey 1966-; Webster, Paul 1952-; Schwimmer, David 1966-; Paltrow, Gwyneth 1972-; Rapaport, Michael 1970-; MiraMax (Burbank, California Miramax Home Entertainment, 1996)
Aspiring architect Tom Thompson (David Schwimmer) is told by mysterious Ruth Abernathy (Barbara Hershey) that his best friend, "Bill," has taken his own life. Except that Tom has never met Bill and neither have his incredulous friends. So when Tom foolishly agrees to give the eulogy at Bill's funeral, it sets him on a collision course with Ruth -- who is revealed to be Bill's oversexed mother -- and Julie DeMarco (Gwyneth Paltrow), the longtime crush Tom hasn't seen since they were teens.
Casting by Billy Hopkins, Suzanne Smith, Kerry Barden ; Music Supervisor, Peter Afterman ; Costume designer, Donna Zakowska ; Music by Stewart Copeland ; Editor, Stan Salfas ; Production design by Robin Standefer ; Director of photography, Robert Elswit ; Co-producer, Jason Katims ; Executive producer, Bob Weinstein.
David Schwimmer, Gwyneth Paltrow, Michael Rapaport, Toni Collette, Carol Kane, Bitty Schram, Barbara Hershey.
VHS format.
In English.
Keywords: Comedy films